The influence of service quality and promotion on e-wallet user interest in Daerah Istimewa Yogyakarta - Sri Suryaningsum; Dyah Ayusulistyaningrum (Proceeding International Conference on Accounting and Finance, 2025)
This research aims to empirically test the influence of service quality and promotion variables on e-wallet users. These two variables are considered important because there were changes in transaction volume in the period 2016 to 2022. This research uses primary data. The research was conducted in the Daerah Istimewa Yogyakarta Province during 2024. The research object was not limited to a particular e-wallet brand so that researchers could get an overview of e-wallet use in general. The Daerah Istimewa Yogyakarta was chosen for reasons, namely: (1) Yogyakarta as a student city has many young people who tend to easily adapt to new technology, especially e-wallets; (2) Yogyakarta has become one of the regions that has experienced the development of non-cash e-wallet payments since 2018; and (3) There is still a need for research regarding the use of e-wallet transactions which represent a regional (not national) scope. The research sample was 150 people. Data analysis uses multiple linear regression tests. The result is that the service quality and promotion variables have a significant effect on e-wallet user interest. Calculation of the coefficient of determination shows that service quality and promotion have an influence of 32.9% on e-wallet user interest. This research provides benefits for e-wallet entrepreneurs to continually improve service quality and provide efficient promotions. This is important in order to maintain consumer interest in using e-wallets sustainably.